Optimizing Power Flow in Photovoltaic-Hybrid Energy Storage Systems: A PSO and DPSO Approach for PI Controller Tuning - Samira Heroual; Belkacem Belabbas; Yasser Diab; Mohamed Metwally Mahmoud; Tayeb Allaoui; Naima Benabdallah (International Transactions on Electrical Energy Systems)
This paper focuses on developing power management strategies for hybrid energy storage systems HESSs combining batteries and supercapacitors (SCs) with photovoltaic (PV) systems. The proposed control scheme is based on proportional-integral (PI) controllers optimized with particle swarm optimization (PSO) and duplicate particle swarm optimization (DPSO) algorithms. The aim is to reduce peak current and the energy management system’s response time while enhancing the system’s stability during the charging and discharging of the HSS under various operating conditions. A comparative study with other tuning methods is presented to demonstrate the effectiveness of the proposed DPSO algorithm in particle duplication, population diversity, and the convergence speed toward the global optimum, enhancing the overall system’s performance. The results demonstrate the feasibility and robustness of the PI−DPSO in providing quick and accurate responses even under variable load, variable solar irradiations, and variable temperature, thus enhancing the dynamic response of the SC and reducing battery stress, resulting in a longer lifespan for the HESS.